Learning disabilities and reading comprehension of students in primary school and the role of ICTS - Gkora, Vana; Stathopoulou, Agathi (Eximia, 2022)
A reader, a text, and an activity are dynamically interlinked in various ways through the pre-reading, while-reading, and post-reading stages. This article aims to analyze the correlation between reading comprehension and learning disabilities in students in the early primary school grades, as well as ways to assess reading comprehension in this age group.